2014
DOI: 10.1183/09031936.00139813
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps in bronchial aspirates: a quantitative analysis

Abstract: Neutrophil extracellular traps (NETs) are structures composed of DNA and granular proteins, which rapidly trap and kill pathogens. The formation of NETs has been detected during infection in animal experiments, but their role in humans is unclear. The purposes of this study were to quantitatively evaluate the production of NETs during acute respiratory infection and to study the relationship between the NET length and various inflammatory mediators.We examined bronchial aspirates collected from nine intubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
2
18
0
1
Order By: Relevance
“…However, the timing of NET formation triggered by stimuli in vivo is unclear. As we reported previously, the maximum amount of NET release was observed on the day following the development of bacterial pneumonia, whereas the level of pro-inflammatory cytokines in the blood was most abundant on the day of onset [13]. The release of NETs via pro-inflammatory stimuli might be delayed in critical situations in humans when compared with that in vitro.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…However, the timing of NET formation triggered by stimuli in vivo is unclear. As we reported previously, the maximum amount of NET release was observed on the day following the development of bacterial pneumonia, whereas the level of pro-inflammatory cytokines in the blood was most abundant on the day of onset [13]. The release of NETs via pro-inflammatory stimuli might be delayed in critical situations in humans when compared with that in vitro.…”
Section: Discussionsupporting
confidence: 55%
“…The amount of NETs appeared to increase after clinical improvement in cases 1 (on day 12) and 2 (on day 17). We previously reported that the length of NETs in tracheal aspirates initially increased and then shortened during acute respiratory infection, and this correlated with the level of pro-inflammatory cytokines (such as interleukin-8 or CXC ligand-2) in the blood [13]. The association between interleukin-8 and NETs was also reported in ventilator-associated pneumonia [9].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…NETs are also known to be active in such infectious lesions as acute appendicitis and experimental models of shigellosis, necrotizing fasciitis and pneumonia [2, 5, 7, 16]. Hamaguchi et al and Hirose et al demonstrated NETs in the sputum sampled from patients with acute respiratory infection [17, 18]. LF, an iron-containing red protein in milk, has been utilized as a quantitative biomarker for inflammatory bowel diseases, such as ulcerative colitis and Crohn’s disease [33].…”
Section: Discussionmentioning
confidence: 99%